Penerapan Model Student Facilitator and Explaining Untuk Meningkatkan Hasil Belajar dan Respon Siswa Kelas XI SMA - Siti Fatimah*; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni (Universitas Syiah Kuala, 2022)
Direct experience in science learning should improve the student's skill in constructing, compreheding, and applying the concept that has been taught. Student facilitator and explaining learning is one of the cooperative learning models, that improve the students' activeness. This research aims is to find out the implementation of student facilitator and explaining learning model towards students' learning outcome on the blood circulatory system material to the eleventh-grade students of SMA Negeri 1, Sungai Raya. This research is a quantitative research with a quasi-experimental method with a non-equivalent as the control group. The sample of this research consists of two classes which are second eleventh grade science as the experiment class and third eleventh grade science as the control class. The sampling technique used in this research is intact group. The tools of collecting data include the students' learning outcome and a questionnaire sheet to find out the students' responses. The data analysis result shows, the score of the learning outcomes obtained by using student facilitator and explaining learning model is 16.08 higher than the conventional learning which is 14.17. Based on the t-test, it was found that thit ttab, that was 3.13 1.997, which means there was a significance difference between the learning outcome in the post-test average result of the experiment class and control class at 5% degree. The average percentage of students' response which taught by using the student facilitator and explaining learning model is 87.52% which can be classified as very high. This average percentage result of the students' response shows that the implementation of student facilitator and explaining learning model gives positive outcome to students' response on the blood's circulatory system material of the eleventh -grade students of SMA Negeri 1 Sungai Raya. The conclusion of the research was the implementation of student facilitator and explaining learning could improve the learning outcome and responses towards the blood circulatory system material for grade XI students